Volcanoes - Gilbert, Sara (Gilbert, Sara. Earth rocks!., 2018)
An elementary exploration of volcanoes, focusing on the geological evidence that helps explain how and where they form and spotlighting famous examples, such as Hawaii's Mauna Loa.